Dopamine transporter (DAT1) gene in combat veterans with PTSD: A case-control study. (April 2021) - Zuschlag, Zachary D.; Compean, Ebele; Nietert, Paul; Lauzon, Steven; Hamner, Mark; Wang, Zhewu
Highlights: First DAT1 candidate gene study conducted in Veterans with PTSD. Case-control study with both PTSD and control cases having previous exposure to combat traumas. Absence of DAT1 10R/10R genotypes was associated with PTSD diagnosis compared to no PTSD diagnosis. DAT1 genotype was associated with significant differences in mean total CAPS scores. Abstract: The dopamine transporter ( DAT1 ) gene has been postulated to be involved in PTSD; however, existing studies have shown inconsistencies when examining genotypic and allelic associations. The primary objective of this study was to examine whether DAT1–40bp-VNTR ( DAT1) 9R polymorphism might increase the risk of PTSD development in combat veterans, utilizing a case-control gene association study with both control and PTSD cases having previous exposure to combat traumas. Participants with PTSD (N   =   365) and combat-exposed controls without PTSD (N   =   298) were included in analysis. After controlling for race, sex and age, when dichotomized, absence of DAT1 10R/10R genotypes was associated with PTSD diagnosis compared to no PTSD diagnosis; these results were not statistically significant when trichotomized 10R/10R, 10R/X, 9R/9R. Similarly, odds ratio for absence of 10R/10R genotype showed a statistically significant increase in the risk of developing PTSD. DAT1 genotype was also associated with statistically significant mean total CAPS scores, both when dichotomized and trichotomized. In conclusion, our results indicate that the absence of 10R/10R is associated with an increased risk of PTSD and higher CAPS total scores.